Giải pháp nâng cao nhận thức bảo vệ môi trường cho học sinh thông qua dạy học tích hợp trong phân môn Địa lí cấp trung học cơ sở - Đào Ngọc Bích, Đào Ngọc Bích; Nguyễn Minh Tý, Nguyễn Minh Tý (Tạp chí Giáo dục, 2026)
In the context of climate change today, environmental education has become an important factor contributing to raising awareness among younger generations. Especially in student education, according to the 2018 General Education Program, there have been significant advances in integrating environmental education, but the actual implementation still faces many challenges. This study indicates that integrating environmental education into History and Geography at the lower secondary level is feasible. Environmental topics can be integrated through themes such as climate, topography, and biodiversity. As a result, students develop both general and subject-specific competencies associated with environmental protection. The research findings propose methods for teachers to effectively integrate environmental education into Geography at the lower secondary level. The study also opens up new approaches to improving the quality of environmental education in the future.